Reconfiguração do espaço urbano de Araxá (MG) no período de 2001 a 2019: implicações da mineração e atuação dos agentes econômicos, políticos e sociais - Leite, Luis Guilherme Ferreira (2020)
A vast array of economic activities are consequences of the capitalist system that operates in a globalized context, and mining is one of them. Mining activity deals with the extraction of products from the soil and, when benefited, such products can improve the way of life of the global community. Recent events in the Brazilian territory have put this economic activity in the spotlight due to the risks present in mining, mainly with regard to tailings dams. Existing in different parts of the world, mining can be found in multiple locations and contexts, including Brazilian urban areas. Therefore, this paper addresses the relationship between the growth of urban spaces and mining activity, a topic that has been scarcely explored in Geography graduate work, according to CAPES Thesis and Dissertation Portal. Thus, this paper aims at analyzing the reconfiguration of Araxá's urban space - a city with an estimated population of 106K inhabitants - and the effects of mining between 2001 and 2019. As such, it is intended to discuss the theoretical and conceptual aspects of the relationship between urban space and mining; contextualize socioeconomic developments based on data available from official agencies; characterize the urban evolution of Araxá since the consolidation of mining activities in the early 2000s and its impacts on the urban space, with emphasis on the real estate market and trading and services activities (especially on the tourism sector). In order to achieve the main objectives, the methodology includes a bibliographic survey and a bibliometric study on CAPES Thesis and Dissertations Portal, documentary research, semi-structured interviews with key actors, field research and the elaboration of graphic and cartographic materials. It was found that the mining activity is responsible for the solid economy of Araxá, and that it enabled the growth and dynamism of the tertiary sector, including a strong retail market and a well-established service sector. In addition, the growth of activities related to retail and the agricultural sector granted a new picture for the economy of Araxá, which has been based on mining since 1955. When it comes to urban growth, the organization of urban space is perceived in an orderly manner, in well-defined legislation based on the Strategic Master Plan. The rapidly growing urban space, especially the northern part of the city, is the result of a solid economy due to mining and other sectors that make Araxá an important urban center in the state of Minas Gerais.